NCOG-08. BIOPSY-ONLY GLIOBLASTOMA (BO-GBM) AS A HETEROGENEOUS GROUP OF PATIENTS. (12th November 2021) - Harlay, Vincent; Loundou, Anderson; Boucard, Céline; Petrirena, Gregorio; Barrie, Maryline; Campello, Chantal; Autran, Didier; Padovani, Laeticia; Figarella, Dominique; Boissonneau, Sébastien; Dufour, Henry; Baumstark, Karine; et al.
Abstract: BACKGROUND: "Biopsy-only" glioblastoma is associated with a heterogeneous functional and survival outcome. It is an understudied group of patients which has been reported to represent 21% of histologically confirmed GBM in the US National Cancer Data Base. Pattern of care included radiotherapy-temozolomide (RT-TMZ) completed in 15% of patients, any other form of oncologic treatment in 60%, and supportive care alone in 25% of patients. Our objective was to explore treatment and prognosis of BO-GBM. MATERIAL AND METHODS: Patients with BO-GBM included in a prospective regional glioma SIRIC cohort in 2014-2017 were retrospectively reviewed for patient characteristics, MRI finding, treatment allocation and delivery. PFS and OS were analyzed. RESULTS: Of 535 patients included in the cohort, 449 patients were included at initial surgery, of which 158 patients (35%) underwent biopsy only. Of 158 patients, 18 were excluded for missing data leaving 139 patients for the present analysis. Fifty-four (39%) were referred to RT-TMZ, 68 (49%) considered unfitted for RT received chemotherapy upfront (CT-UF), 17 (12%) were referred to palliative care. Groups differed at baseline for age (mean 60 and 68 years, for RT-TMZ, CT-UF respectively); KPS (70, 60 for RT-TMZ, CT-UF); mean tumor surface (793, 1420 mm2 for RT-TMZ, CT-UF); and tumor extension (bilateral in 6.4% and 29.3% for RT-CT and CT-UF respectively). Median OS was 14 months (95% CI, 9.65-18.71) and 8 months (95% CI, 4.62-7.67) for RT-TMZ, CT-UF respectively. CONCLUSION: Inoperable GBM constitute a large and heterogeneous population in which one third of patients are amenable to standard of care, with survival outcome close to the one of patients who underwent surgery. Patients considered unfit for RT-CT at diagnosis exhibit a poor survival outcome. Thus, reliable criteria are needed to help selecting patients for adequate treatment while new strategies are warranted for BO-GBM unfit for RT.